The NMDAR/TRPM4 death complex is a major promoter of disease progression in the 5xFAD mouse model of Alzheimer’s disease - Yan, Jing; Yang, Xiaohui; Li, Guilin; Ramirez, Omar; Hertle, Anna M.; Chen, Zhe-Yu; Bading, Hilmar (Molecular psychiatry, 2025)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder, characterized by cognitive decline and neuronal degeneration. The formation of amyloid β plaques and neurofibrillary tangles are key morphological features of AD pathology. However, the specific molecules responsible for the cell destruction triggered by amyloid β and tau proteinopathies in AD has not yet been identified. Here we use the 5xFAD mouse model of AD to investigate the role of a recently discovered death signaling complex which consists of the extrasynaptic N-methyl-D-aspartate receptor (NMDAR) and the transient receptor potential cation channel subfamily M member 4 (TRPM4). The NMDAR/TRPM4 death complex is responsible for toxic signaling of glutamate, which has been implicated in AD pathogenesis. We detected an increase in NMDAR/TRPM4 death complex formation in the brains of 5xFAD mice. This increase was blocked by the oral application of FP802, a small molecule TwinF interface inhibitor that can disrupt and thereby detoxify the NMDAR/TRPM4 death complex. FP802 treatment prevented the cognitive decline of 5xFAD mice assessed using a series of memory tasks. It also preserved the structural complexity of dendrites, prevented the loss of synapses, reduced amyloid β plaque formation, and protected against pathological alterations of mitochondria. These results identify the NMDAR/TRPM4 death complex as a major promoter of AD disease progression, amplifying potentially self-perpetuating pathological processes initiated by amyloid β. TwinF interface inhibitors offer a novel therapeutic avenue, serving as an alternative or complementary treatment to antibody-mediated clearing of amyloid β from AD brains.
Online veröffentlicht: 26. August 2025
Gesehen am 09.01.2026